ROLE OF CT SCAN EXAMINATION ON COVID-19 - Deasy Umi Hajarsari (Indonesian Journal of Multidisciplinary Science, 2022)
Coronavirus disease 2019 (COVID-19) is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The role of radiology has a very important role in diagnosis and evaluation. CT scan has a potential role in diagnosing and complications of COVID-19, such as acute respiratory distress syndrome, pulmonary embolism, and heart failure, while its role in determining prognostics requires further investigation. The images on a COVID-19 CT scan generally show ground glass opacities, consolidation, air bronchogram and poving stone. CT scan examination can be used in the use of triage in the hospital in enforcing COVID-19 patients who need immediate treatment. The use of radiological examinations in combination with RT-PCR can help diagnose and manage COVID-19.